2015
DOI: 10.1159/000439039
|View full text |Cite
|
Sign up to set email alerts
|

Circannual Testis Changes in Seasonally Breeding Mammals

Abstract: In the non-equatorial zones of the Earth, species concentrate their reproductive effort in the more favorable season. A consequence of seasonal breeding is seasonal testis regression, which implies the depletion of the germinative epithelium, permeation of the blood-testis barrier, and reduced androgenic function. This process has been studied in a number of vertebrates, but the mechanisms controlling it are not yet well understood. Apoptosis was assumed for years to be an important effector of seasonal germ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 104 publications
0
26
0
1
Order By: Relevance
“…Drosophila lines exposed to X-ray irradiation, for example, evolved increased resistance to DNA damage but this resistance was lost after cessation of exposure to X-ray, further supporting the idea that increased DNA maintenance is costly (36). The cost of germline maintenance can also be inferred from the fact that many mammals and birds reduce the size of their germ line to a minimum outside the breeding season (37,38) and that germline ablation in C. elegans nematodes and male D. melanogaster fruitflies results in an increase in lifespan (29,39). Further indirect evidence comes from studies showing that castration in males results in a significant increase in lifespan in rats (40) and humans (41).…”
Section: Resultsmentioning
confidence: 90%
“…Drosophila lines exposed to X-ray irradiation, for example, evolved increased resistance to DNA damage but this resistance was lost after cessation of exposure to X-ray, further supporting the idea that increased DNA maintenance is costly (36). The cost of germline maintenance can also be inferred from the fact that many mammals and birds reduce the size of their germ line to a minimum outside the breeding season (37,38) and that germline ablation in C. elegans nematodes and male D. melanogaster fruitflies results in an increase in lifespan (29,39). Further indirect evidence comes from studies showing that castration in males results in a significant increase in lifespan in rats (40) and humans (41).…”
Section: Resultsmentioning
confidence: 90%
“…This is necessary if the non-breeding period is long enough to make testis regression efficient in terms of energy saving, as spermatogenesis is too expensive to be maintained when it is not needed [ 6 ]. After the study of a number of seasonal breeding mammals, it seems evident that there is not a unique mechanism of testis regression, existing two main cellular processes by which germ cells are massively depleted: apoptosis and desquamation [ 7 ]. However, more species must be studied to determine their relative prevalence and, maybe, to discover new testis regression mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to germ cells, Leydig cells also show species-specific differences in the regressed testis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In seasonal reproducers, the mechanisms regulating the process of germ cell desquamation during testis regression is still poorly known. These wild animals have strong hormonal response to the natural succession of breeding and non-breeding seasons, showing, during the non-breeding season, very low circulating and intra-testicular testosterone levels (for a review, Jimenez et al 2015). Both testosterone and gonadotropins are known to regulate the expression of cell adhesion proteins in the testis , Tarulli et al 2008, McCabe et al 2010) and, in testosteronesuppressing experiments in the rat, it has been shown that dissociation of the adhesion complexes at the apical ES contributes to the massive sloughing of immature spermatids (Zhang et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal reproduction in the non-equatorial regions of the planet is an adaptive strategy aimed at assuring newborns the best environment for survival. During the non-reproductive season, block of the ovarian function and reduction or interruption of the testis activity determines the inability to produce offspring (for a review Jimenez et al 2015). Spermatogenetic arrest has been described in several mammalian species including the Iberian mole (Dadhich et al 2010(Dadhich et al , 2013, the hamster (Bex & Bartke 1977), the black bear (Tsubota et al 1997), the white-footed mouse (Young et al 1999) and the large hairy armadillo Chaetophractus villosus whose seminiferous epithelium undergoes, once a year, rapid regression (Luaces et al 2013(Luaces et al , 2014.…”
Section: Introductionmentioning
confidence: 99%